THE DEVELOPMENT OF ELECTONE TEACHING - Yijia, Li; Banchongsilpa, Orawan Banchongsilpa (Asia Pacific Journal of Religions and Cultures, 2025)
The development of electone teaching in China reflects the country's adaptation to global musical influences, integrating modern electronic instruments into a traditionally rich musical culture. While rooted in a predominantly secular society, electone education aligns with Confucian values of structured learning and discipline, blending Western pedagogy with China's cultural beliefs around education. This article explores the evolution of electone teaching in China, tracing its introduction and integration into the country's music education system. As an electronic instrument with origins in Japan, the electone has gained popularity in China, reflecting a broader trend of incorporating global musical elements into Chinese education. The article examines the pedagogical approaches to electone instruction, highlighting the ways in which traditional Chinese cultural values, such as discipline and structured learning, have shaped its teaching methods. Additionally, it discusses how electone teaching aligns with China's modern, secular context, while still allowing for creative expression and adaptation to Western musical influences. Through this analysis, the article provides insights into the significance of electone education within the broader landscape of music education in China. This article presented (1) the development of electone teaching in China, (2) establishing the electone in China, (3) developing the curriculum, developing the teaching practice, and electone stage performance.